Anthropometric profile of the top-class female handball players participating in the Olympic Games Tokyo 2020 - Krawczyk, P.; Sienkiewicz-Dianzenza, E. (Biomedical Human Kinetics, 2023)
Study aim: The aim of this study was to try to determine the factors that differentiate the height, weight, BMI, and age of high-level female handball players participating in the Tokyo 2020 Olympic Games.